2022
DOI: 10.1007/s00405-021-07219-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium alginate versus proton pump inhibitors for the treatment of laryngopharyngeal reflux: a non-inferiority randomized controlled trial

Abstract: Purpose Proton pump inhibitors (PPIs) are commonly prescribed for laryngopharyngeal reflux (LPR), but their efficacy remains debated. Alginates is an option for the treatment of LPR with few adverse effects. The study aimed to investigate the non-inferiority of an alginate suspension (Gastrotuss®) compared to PPIs (Omeprazole) in reducing LPR symptoms and signs. Methods A non-inferiority randomized controlled trial was conducted. Fifty patients with laryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(72 reference statements)
0
6
0
1
Order By: Relevance
“…Notably, all patients received lifestyle modifications, which could account for the lack of a difference between groups. In a non‐inferiority randomised controlled trial of 50 patients with RSI ≥ 13 and RFS ≥ 7, Pizzorni et al 116 demonstrated that patients treated with alginates (Gastrotuss 20 mL, three times per day) or omeprazole 20 mg daily had significant improvement in mean RSI, and alginates were non‐inferior to PPIs.…”
Section: An Overarching Perspective On Goals Of Managementmentioning
confidence: 99%
“…Notably, all patients received lifestyle modifications, which could account for the lack of a difference between groups. In a non‐inferiority randomised controlled trial of 50 patients with RSI ≥ 13 and RFS ≥ 7, Pizzorni et al 116 demonstrated that patients treated with alginates (Gastrotuss 20 mL, three times per day) or omeprazole 20 mg daily had significant improvement in mean RSI, and alginates were non‐inferior to PPIs.…”
Section: An Overarching Perspective On Goals Of Managementmentioning
confidence: 99%
“…Alginate forms a gelatinous layer on top of the gastric contents and makes a mechanical barrier, thereby reducing contact between the reflux contents and esophageal mucosa. Alginate also has a significant inhibitory effect on pepsin, and is, according to some research, non-inferior to PPI [13,29]. Other noninvasive treatment options include using external upper esophageal sphincter compression device.…”
Section: Treatmentmentioning
confidence: 99%
“…Laryngopharyngeal reflux (LPR) is an inflammatory condition where stomach contents move in a retrograde fashion, enter and affect the upper aero-digestive tract 1 causing a variable presentation of symptoms that can include dysphonia (chronic or intermittent), excessive throat clearing, globus sensation, chronic cough, vocal fatigue or vocal effort, sore throat and dysphagia among others 2 , 3 . The prevalence of LPR-related symptoms ranges from 10% to 30% in otolaryngology department consultations, reaching up to 50% in clinical laryngology practices 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence may be increasing given the ever-worsening lifestyle and dietary habits of most Western cultures 4 . Treatment options for LPR include diet and lifestyle modifications, proton pump inhibitors (PPIs), H2 blockers and/or alginate or magaldrate 3 .…”
Section: Introductionmentioning
confidence: 99%